Novel Methodology for the Selection of Cases from MICS data for Growth Charts Development Based on WHO Criterion - Muhammad Aasim, Sohail Chand (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The growth charts are very important for monitoring a child growth and for estimation of stunting and wasting in a country. This can be done efficiently if the references and standards for growth monitoring are correct. Aim: To devise the methodology of selection of cases from multiple indicator cluster survey (MICS) data available worldwide under UNICEF for most of the developing and non-developed countries. Methods: This methodology was devised during 1st January 30th June 2022 in College of Statistical Sciences, University of the Punjab, Lahore. The three rounds of MICS, i.e. the 4th, 5th and 6th, were evaluated for their eligibility to develop a standard growth chart for children under two year’s age. The criteria needed to be met were, singleton, full term birth up to 4thorder, exclusive breastfeeding for 4-6 months, continuing breastfeeding till one year age. Belonging to affluent socioeconomic status, not having any severe illness and born to non-smoking mothers. The MICS data is available in the format of SPSS data files. These files have been explored for the variables answering these questions directly or indirectly. Results: The MICS rounds 4 and 5 were discarded after having a detailed view, as they were not fulfilling the WHO criteria due to missing information for several important variables. The round 6 was found to have direct information on many of the variables, i.e., singleton, full-term, birth order, family size, mother smoking status while some other variables i.e. exclusive breast feeding, severe illness, and not belonging to deprived class were objectively created using some other variables existing in MICS data Conclusion: This methodology for selection of cases, can provide us children with height, weight, age and gender of children as per WHO criteria required to meet for development of the standard growth chart for children under two years age. Keywords: WHO criteria, Pediatric growth standards, MICS